Field notes contributed by Dennis Henrickson, spring 1997 - Henrickson, Denniset al (1997)
List of birds and locations contributed by Dennis Henrickson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1997. Epson - sheet feed/flatbed